Real versus financial frictions to capital investment - Nihal Bayraktar; Plutarchos Sakellaris; Philip Vermeulen (European Central Bank (ECB), 2005)
We formulate and estimate a structural model of firm investment behavior that specifies the exact channel through which financial frictions bite. The model also allows for the existence of both convex and non-convex costs to adjusting capital. Essentially, we move beyond simply testing and rejecting a neoclassical model without frictions. Our quantitative estimates show that both real and financial frictions have an important effect on firm investment dynamics.
Keywords: E22; 330; adjustment costs; financing constraints; Investment; Investitionsentscheidung; Unternehmensfinanzierung; Rentabilität; Schock; Theorie